The Effect of Inclusive Leadership on Employee Performance Mediated through Innovative Behavior and Work Engagement - Raditya Syafa Ramadhan Maatita; Rini Juni Astuti (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In today’s dynamic public sector, fostering effective leadership is crucial to improving employee performance and organizational outcomes. This study aims to investigate the effect of inclusive leadership on employee performance by integrating innovative behavior and work engagement as mediating variables in a public sector setting. A quantitative approach with an explanatory research design was employed. Data were collected through a structured questionnaire distributed to 120 employees of the Regional Office of the Ministry of Religious Affairs in the Special Region of Yogyakarta, selected using purposive sampling. The analysis was conducted using the SEM-PLS method. The results indicate that inclusive leadership has a positive and significant influence on innovative behavior, work engagement, and employee performance. Furthermore, innovative behavior and work engagement also show positive and significant effects on employee performance. Mediation testing confirms that both innovative behavior and work engagement serve as important mediators in the relationship between inclusive leadership and employee performance. These findings suggest that inclusive leadership becomes more effective in enhancing employee performance when supported by employees’ psychological engagement and innovative actions. This study contributes to the development of inclusive leadership theory and offers practical implications for human resource management practices within public sector organizations.